Cluster analysis of competitiveness, self-improvement and self-creation potential - Juha, Nadzeja D. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
In this research, we make predictions that for creative and self-creative activity of the teacher and the student as a future specialist it is important to create conditions for the determination of further self-promotion and self-development of the student with the use of his own potential opportunities and intellectual resources, improving not only effciency in the activity, but also the desire of the teacher and of the student to self-realization, competitiveness through education. Our main long-term studies, proven by factor analysis showed that the creation of a productive subject of education depends on the self-realization and self-improvement, development of imagination, high creativity, ability to solve non-standard situations, the correlation between creativity and the acquisition of the motive of knowledge management – co-management – selfmanagement, focus on communication and work, values, synergy. It is proved that for the creation the most important qualities of the person’s ability are to lead, to support, to empathize, to be sociable and intelligent.
Keywords: creative and selfcreative activity; teacher; student; future specialist; self-realization; striving and readiness of the student for the self-realization in his future creative activity; competitiveness; creative activity